Increased Productivity of Agathis labillardierei Species Growth with ZPT-Cytosine Injection and Coffee Waste Fertilizer - Markani, Markani; Savira Dyah Istiqlawati; Sevina Ayu Andini; Safitri, Ananta Ria (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Various industrial sectors widely use Damar Putih trees, particularly as a source of resin raw materials. However, the high demand for resin from this species is not matched by its declining growth rate and productivity. Based on previous research, it has been found that fermented coffee waste used as liquid fertilizer can significantly improve the quality and productivity of tomato fruits. Therefore, this study aims to conserve the White Damar species using ZPT-Cytosine injection and coffee waste fertilizer. This study employs an experimental method designed to enhance the growth productivity of the Agathis labillardierei species through the application of cytosine growth regulator injections and the use of organic fertilizer made from coffee waste (coffee waste fertilizer). The results indicate that this approach successfully increased the average stem growth rate from 8 cm/month to 10 cm/month, with plant height reaching 80 cm within six months. The use of coffee waste as organic fertilizer not only contributes to the availability of essential nutrients but also serves as an environmentally friendly waste management solution.